Exploring the evolution of a persistent viral infection of Drosophila melanogaster across time and space - Keene-Snickers, Alexandra Harrington, author; Stenglein, Mark, advisor; Abdo, Zaid, committee member; Foy, Brian, committee member; Balgopal, Meena, committee member (Colorado State University. Libraries, 2025)
Efforts to characterize the viral communities of organisms across the tree of life have uncovered diversity that is magnitudes greater than previously thought. It is now understood that organisms can be infected with many viruses at once and that many of these infections have limited or no impact on the hosts health. Some of these infections are persistent, lasting the lifetime of the host. The basic biology and evolution that allow these viruses to persist are not well understood but are important to create a more realistic picture of host-virus interactions. In this dissertation I have employed the model organism Drosophila melanogaster and its viral symbiont, galbut virus, to study the evolution of persistent viral infections. In Chapter 1, I provided a brief background on current methods to study viruses over time and space. I also discussed the characteristics of persistent viral infections as they are currently understood. Finally, I provided rationale for the use of the D. melanogaster-galbut virus model as an appropriate system to study persistent viral infections and their evolution. In Chapter 2, I utilized old Drosophila museum specimens to study viral and host RNA from samples over 100-years-old. This work shed light on the evolutionary history of galbut virus and revealed that RNA survives in dried samples better than prevailing dogma would suggest. In Chapter 3, I developed two fly traps for the effective capture of wild D. melanogaster by untrained participatory scientists. These traps were instrumental to the collection of wild specimens for my work in Chapter 4. In Chapter 4, I broadly sampled flies across the USA and generated several hundred new galbut virus sequences. This enabled me to characterize galbut virus diversity, evolutionary patterns, and genotype-phenotype associations. In summary, my dissertation explores the evolution of a persistent viral infection using virus sequences diverse in time and space. The methods employed provide insight into the forces at work in persistent viral infections.
Keywords: Drosophila melanogaster; virus evolution; persistent virus; ancient RNA